PENGARUH KREATIVITAS DAN INOVASI TERHADAP KEUNGGULAN BERSAING (STUDI KASUS SALES WEDDING HOTEL INTERCONTINENTAL BALI RESORT) - I Gusti Ayu Agung Berlian Saputra; Ni Luh Gde, Sri Sadjuni; witarsana, I Gusti Agung Gede (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Changing customer demands have an impact on the company assessment given, requiring the application of creativity and innovation. Therefore, applying creativity and innovation is very important. The challenge felt by employees who work as wedding sales is that they must have the ability to design creative and innovative facilities and services in order to compete in competitor markets. This research was conducted at the InterContinental Bali Resort hotel. This research aims to determine the influence of creativity and innovation on competitive advantage. This research was analyzed using the Statistical Program for Social Science (SPSS). This type of research data is descriptive quantitative with data collection techniques using questionnaires. The population is consumers who have used InterContinental Bali Resort wedding services in the 2019-2024 period. The sample was 145 respondents. This research data analysis is a multiple linear regression analysis method. Then the statistical method used is the partial test (t) to test the effect partially and the simultaneous test (F) to test the effect simultaneously. The results of this research show that creativity and innovation partially and simultaneously have a positive and significant effect on the competitive advantage of wedding sales at the InterContinental Bali Resort hotel. The factors that influence the competitive advantage of InterContinental Bali Resort's wedding hotel sales show results with a coefficient of determination value of 62.8%. Overall the independent variables have a mutual relationship, while the remaining 37.2% is influenced by other variables that are not. included in this study.